BAGAIMANA PENGARUH DIGITAL MARKETING DAN CAPACITY BUILDING TERHADAP KINERJA UKM DI KOTA MEDAN? - Fenny Krisna Marpaung; Hendra Jonathan Sibarani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
The aim of the study was to study and analyze the effect of digital marketing and capacity building on the performance of SMEs in Medan City simultaneously, examine and analyze the effect of digital marketing on the performance of SMEs in Medan, study and analyze the influence of capacity building on the performance of SMEs in Medan. The method used to analyze the data is multiple linear regression analysis. The results of research conducted by researchers prove that there is an influence of digital marketing on the growth of SMEs. This can be seen from the results of the partial test (t-test) where the value of tcount> t table (8.962> 1.979) and the significance value of 0,000 <0.05. So the results of the study reject H0 and accept Ha. The results of the research prove that there is an influence of capacity building on the growth of SMEs. So the results of the study reject H0 and accept Ha. The results of this study mean that SMEs need capacity building or capacity building.